PENGARUH KEBIJAKAN DESENTRALISASI FISKAL DAN PERGESERAN SEKTORAL TERHADAP KETIMPANGAN PENDAPATAN ASLI DAERAH AREA SUMBAGSEL DALAM PERSPEKTIF EKONOMI ISLAM TAHUN 2015-2023 - Kurniawan, Muhammad; Noviarita, Heni; Anriyani, Yuyun (JURNAL ILMIAH EDUNOMIKA, 2025)
Inequality is a more complex problem than poverty. High inequality will gradually become an obstacle to economic growth. Income inequality is a situation where the distribution of people's income shows an unequal situation and is more favorable to certain groups. This research wants to know the effect of fiscal decentralization policies and sectoral shifts on regional original income inequality in South Sumatra. By using econometric methods through panel data equations in the 2015-2023 period, this research finds that fiscal decentralization and shift policies can reduce regional original income inequality.